2013
DOI: 10.1248/bpb.b12-00910
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Erythraline on Toll-Like Receptor Signaling Pathway in RAW264.7 Cells

Abstract: Erythraline, isolated from the bark of Erythrina crista-galli which are used as Brazilian medicine plant for the treatment of inflammation diseases, suppressed nitric oxide (NO) production and induction of inducible nitric oxide synthase (iNOS) expression in RAW264.7 cells stimulated by lipopolysaccharide (LPS). Because of Toll-like receptor (TLR) 4 and its signal transduction are indispensable to the production of NO and iNOS expression by LPS, we investigated the effects of erythraline on TLR signaling molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The cells were cultured at 37˚C in an atmosphere containing 5% CO 2 , and different concentrations (150, 300, and 600 mg/l) of SAP-1 and SAP-2 were added. The Griess method was performed to determine the levels of nitric oxide (NO) according to the protocol described in a previous study (14), and the absorbance was read at 540 nm using a microplate reader (Benchmark Plus; Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured at 37˚C in an atmosphere containing 5% CO 2 , and different concentrations (150, 300, and 600 mg/l) of SAP-1 and SAP-2 were added. The Griess method was performed to determine the levels of nitric oxide (NO) according to the protocol described in a previous study (14), and the absorbance was read at 540 nm using a microplate reader (Benchmark Plus; Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…TRAF6 is phosphorylated by IRAKs and binds to Ubc13 and Uev1A to form a complex that activates a mitogen-activating protein kinase kinase (MAPKKK) called transforming growth factor β-activating kinase-1 (TAK-1). Activated TAK-1 phosphorylates MKKs, which are upstream kinases of p38 MAPKs and JNK ( 85 ). p38 is involved in many cellular physiological and pathological processes, including apoptosis, cellular stress, the cell cycle, and the inflammatory response ( 86 ).…”
Section: Tlr Signalling In B Cellsmentioning
confidence: 99%
“…p38 is involved in many cellular physiological and pathological processes, including apoptosis, cellular stress, the cell cycle, and the inflammatory response ( 86 ). In addition, TAK-1 can activate the IκBα kinase (IKK) complex, consisting of the IKKα and IKKβ kinases and the hinge protein IKKγ ( 85 ). Phosphorylation of IκBα leads to its own degradation and the release of NF-κB ( Figure 2 ).…”
Section: Tlr Signalling In B Cellsmentioning
confidence: 99%
“…Taking into account that toll‐like receptors (TLRs) are a key component of inflammatory process, Etoh et al () investigated the effects of erythraline ( 40 ), from E. crista‐galli barks, on TLR signaling molecules. The results suggested that the target molecule involved in erythraline ( 40 ) anti‐inflammatory activity is transforming growth factor‐β‐activated kinase (TAK‐1), a mitogen protein kinase activated by TLR ligants.…”
Section: Preclinical Studiesmentioning
confidence: 99%